2022
DOI: 10.3390/encyclopedia2010028
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Profile of COVID-19 Preventative Strategies

Abstract: The COVID-19 pandemic has caused millions of deaths and has affected most people across the world, either directly or indirectly. Many preventative and therapeutic strategies have been employed since the beginning of the pandemic. With the development of the mRNA vaccine within a year of the start of the pandemic, we are entering a new era of vaccinology, and the adverse event profile of the COVID-19 vaccine is also becoming more apparent with time. While the benefits of the vaccines and other preventative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The incidence of unintentional adverse events, severe adverse events, and serious adverse events recorded within the 28 days after injection, on the other hand, was almost the same in the vaccination and control groups. Cardiac adverse events like pericarditis, AF and myocarditis were reported much more often in patients with second doses of vaccination as reported by the VAERS database [12].…”
Section: Mrna-1273 Mrna Vaccinementioning
confidence: 74%
See 2 more Smart Citations
“…The incidence of unintentional adverse events, severe adverse events, and serious adverse events recorded within the 28 days after injection, on the other hand, was almost the same in the vaccination and control groups. Cardiac adverse events like pericarditis, AF and myocarditis were reported much more often in patients with second doses of vaccination as reported by the VAERS database [12].…”
Section: Mrna-1273 Mrna Vaccinementioning
confidence: 74%
“…Post-vaccination cardiac adverse events have been reported by the vaccine adverse event reporting system (VAERS) database with the highest risk of atrial fibrillation (AF) [12]. Among the vaccines, BNT162b2 has been found to have the highest incidence of AF.…”
Section: Bnt162b2 Mrna Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the scope, it can be divided into three categories: sentiment classification at the word level, sentiment analysis at the sentence level, and sentiment analysis at the sub-sentence or phrase level. [ 36 , 37 ]. The highest level of communication in society is social networking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As of this writing, several vaccines have received FDA approval for use [91][92][93]. A broader review of possible adverse effects associated with the vaccines can be found elsewhere in this volume [94]. Researchers have received questions from patients regarding whether the vaccines themselves can cause otovestibular symptoms or exacerbate preexisting otovestibular diseases.…”
Section: Vaccines For Covid-19mentioning
confidence: 99%